Observational and numerical characterization of a recurrent arc-shaped front propagating along a coronal fan - Sieyra, M. V.; Krishna Prasad, S.; Stenborg, G.; Khomenko, E.; Van Doorsselaere, T.; Costa, A.; Esquivel, A.; Riedl, J. M. (Astronomy and astrophysics (Berlin), 2022)
Context. Recurrent, arc-shaped intensity disturbances were detected by extreme-ultraviolet channels in an active region. The fronts were observed to propagate along a coronal loop bundle rooted in a small area within a sunspot umbra. Previous works have linked these intensity disturbances to slow magnetoacoustic waves that propagate from the lower atmosphere to the corona along the magnetic field. Aims. The slow magnetoacoustic waves propagate at the local cusp speed, which is equivalent to the sound speed in a low- β -regime plasma. However, the measured propagation speeds from the intensity images are usually smaller as they are subject to projection effects due to the inclination of the magnetic field with respect to the line of sight. We aim to understand the effect of projection by comparing observed speeds with those from a numerical model. Methods. Using multi-wavelength data, we determined the periods present in the observations at different heights of the solar atmosphere through Fourier analysis. We calculated the plane-of-sky speeds along one of the loops from the cross-correlation time-lags obtained as a function of distance along the loop. We performed a 2D ideal magnetohydrodynamic simulation of an active region embedded in a stratified atmosphere. We drove slow waves from the photosphere with a three-minute periodicity. Synthetic time–distance maps were generated from the forward-modelled intensities in coronal wavelengths and the projected propagation speeds were calculated. Results. The intensity disturbances show a dominant period between 2 and 3 min at different heights of the atmosphere. The apparent propagation speeds calculated for coronal channels exhibit an accelerated pattern with values increasing from 40 to 120 km s −1 as the distance along the loop rises. The propagation speeds obtained from the synthetic time–distance maps also exhibit accelerated profiles within a similar range of speeds. Conclusions. We conclude that the accelerated propagation in our observations is due to the projection effect.